Association of Leukocytosis with Amphetamine and Cocaine Use - John R. Richards; Valeria F. Farias; Chris S. Clingan (The Scientific World Journal)
Objective. Determining the etiology of unexplained leukocytosis in asymptomatic patients may incur unnecessary testing, cost, and prolonged emergency department stay. The objective was to delineate if use of amphetamines and/or cocaine is a factor. Methods. For two years we reviewed all psychiatric patients presenting for medical clearance with exclusions for infection, epilepsy, trauma, or other nonpsychiatric medical conditions. Results. With a total of 1,206 patients, 877 (72.7%) amphetamines/cocaine-negative drug screen controls had mean WBC 8.4±2.6×103/µL. The 240 (19.9%) amphetamines-positive, cocaine-negative, patients had WBC 9.4±3.3×103/µL (P<0.0001). The 72 (6.0%) amphetamines-negative, cocaine-positive, patients had WBC 7.1±1.8×103/µL (P<0.0001). The remaining 17 (1.4%) amphetamines/cocaine-positive patients had WBC 10.0±4.2×103/µL (P=0.01). Amphetamines-positive patients had a supranormal WBC ratio significantly higher than controls (23.8% versus 14.8%, P=0.001), whereas only one cocaine-positive patient had a supranormal WBC count, with significantly lower ratio (1.4%, P=0.0003). Conclusion. Use of amphetamines, not cocaine, may be associated with idiopathic leukocytosis. This may be explained by unique pharmacologic, neuroendocrine, and immunomodulatory differences.